2010
DOI: 10.1039/c004847j
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel detection of gene expression in single cells using subnanolitre wells

Abstract: The relationship between the expression of particular genes in cells and their impact on phenotypic characteristics is important for understanding how cells regulate responses to their environment. We have developed a microwell-based method to detect copies of mRNA transcripts directly from individual cells by one-step, single-cell, reverse transcription polymerase chain reaction (RT-PCR). Our approach permits the detection of mRNA transcripts of interest for more than 6000 single cells in parallel per assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 21 publications
0
86
0
Order By: Relevance
“…Initial attempts to perform RT-qPCR in low nanoliter volumes were found to produce highly variable results, including nonspecific amplification and inconsistent detection of abundant transcripts (18). Cell lysate dilutions showed that reaction inhibition becomes significant at concentrations in excess of 0.2 cells∕nL, or 10 cells∕50 nL-reaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initial attempts to perform RT-qPCR in low nanoliter volumes were found to produce highly variable results, including nonspecific amplification and inconsistent detection of abundant transcripts (18). Cell lysate dilutions showed that reaction inhibition becomes significant at concentrations in excess of 0.2 cells∕nL, or 10 cells∕50 nL-reaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, these processes are nondestructive, which allows the recovery of viable cells for expansion in vitro, 32,33 or massively parallel detection of expressed mRNA transcripts. 34 The evaluation of the diversity in the humoral, or antibody, response raised in a model vaccination provides a representative problem to illustrate how these interchangeable operations can enable a comprehensive bioanalytical process. 35 We immunized mice with a prime-boost regime using ovalbumin-a model protein designed to mimic a recombinant immunogen in a vaccine-and then collected a series of data for a set of B cells using a combination of image-based cytometry and serial microengraving.…”
Section: Designing Batch Processes For Integrated Single-cell Analysismentioning
confidence: 99%
“…Both of these advantages are very hard to replicate using flow cytometry tools. An additional advantage of the microengraving platform is that it can be modified for PCR-based detection of a few transcripts at the single-cell level (69), although the combination of proteins and transcripts from the same single cells, using microengraved platforms, has not yet been reported. Figure 3 illustrates a microengraving experiment designed to detect antibody-secreting B cells collected from specific locations from a healthy mouse or a mouse model of the autoimmune disorder known as Sjögren's syndrome (68).…”
Section: Tools Using Surface-based Immunoassaysmentioning
confidence: 99%